Structural insights into the inhibition of Zika virus NS2B-NS3 protease by a small-molecule inhibitor - Li, Yan (2020)
Zika virus (ZIKV) infection has become a global public health concern. The viral NS2B-NS3 protease is an attractive antiviral target because of its role in maturation of viral non-structural proteins. Substrate-derived protease inhibitors have been investigated, but it remains challenging to develop them into drugs. Small-molecule inhibitors are of great interest in antiviral drug development. Here we report the structure and dynamics of ZIKV NS2B-NS3 protease covalently bound to a small-molecule inhibitor. Our crystallographic and NMR studies demonstrate that the inhibitor further stabilizes the closed conformation of ZIKV protease. Upon hydrolysis in situ into two fragments, the benzoyl group of the inhibitor forms a covalent bond with the side chain of catalytic residue S135, whereas the second fragment exhibits no obvious molecular interactions with the protease. This study provides a detailed mechanism of action for a covalent inhibitor, which will guide further development of ZIKV protease inhibitors.